2005
DOI: 10.1212/01.wnl.0000161876.20552.aa
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and clinical applications of vestibular-evoked myogenic potentials

Abstract: A recent technique of assessing vestibular function, the vestibular-evoked myogenic potential (VEMP), is an otolith-mediated, short-latency reflex recorded from averaged sternocleidomastoid electromyography in response to intense auditory clicks delivered via headphones. Since their first description 10 years ago, VEMPs are now being used by investigators worldwide, and characteristic changes observed with aging and in a variety of peripheral and central vestibulopathies have been described. Additional methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
293
0
26

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(328 citation statements)
references
References 69 publications
9
293
0
26
Order By: Relevance
“…Seven (88%) of the eight patients had bilateral normal VEMPs, revealing sparing of the inferior vestibular nerve. Thus, an intact inferior vestibular nerve seems necessary to generate benign paroxysmal positional vertigo in the future [30]. In contrast, Murofushi et al [31] reported that eight patients with vestibular neuritis had absence of both click and galvanic VEMPs, indicating that vestibular neuritis may affect inferior division of the vestibular nerve as well.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Seven (88%) of the eight patients had bilateral normal VEMPs, revealing sparing of the inferior vestibular nerve. Thus, an intact inferior vestibular nerve seems necessary to generate benign paroxysmal positional vertigo in the future [30]. In contrast, Murofushi et al [31] reported that eight patients with vestibular neuritis had absence of both click and galvanic VEMPs, indicating that vestibular neuritis may affect inferior division of the vestibular nerve as well.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The initiation of the vestibulo-ocular reflex (VOR) (Halmagyi and Curthoys 1988), caloric irrigation (Bárány 1921), and vestibular evoked myogenic potentials (VEMP) (Welgampola and Colebatch 2005) are now the basis of standard clinical tests whose diagnostic value is based at least partly on the presence of asymmetric responses. The reason that degree of asymmetry is useful in these tests is because the range of normal asymmetry is known.…”
Section: Introductionmentioning
confidence: 99%
“…Most of our understanding of vestibular physiology comes by way of understanding the vestibular control of reflexes including the VOR (Halmagyi and Curthoys 1988;Crane and Demer 1998), postural responses (Liaw et al 2009), andVEMP (Welgampola andColebatch 2005). However, vestibular reflexes and vestibular perception arise from fundamentally different mecha-nisms (Merfeld et al 2005a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, stimuli above 90 dBHL are used 2,[8][9][10][11][14][15][16]18,19,24,[28][29][30][31] . However, in many studies, the threshold is surveyed by means of stimuli of different intensities (with ascending or descending techniques) until the lowest stimulus intensity capable of triggering a response is found 2,21,25,32 .…”
Section: Stimuli Averagingmentioning
confidence: 99%
“…The recording is done by means of averaging or adding, and the parameters used in most studies are equal to or higher than 200 stimuli 2,[8][9][10]14,17,20,26,27,30,31 . In general, the higher the number of stimuli and the lower the shooting rate (number of stimuli per second), the better the recording quality.…”
Section: Stimuli Averagingmentioning
confidence: 99%